Dehydration-Induced Redistribution of Amphiphilic Molecules between Cytoplasm and Lipids Is Associated with Desiccation Tolerance in Seeds - Buitink, Julia (American Society of Plant Physiologists, 2000)
This study establishes a relationship between desiccation tolerance and the transfer of amphiphilic molecules from the cytoplasm into lipids during drying, using electron paramagnetic resonance spectroscopy of amphiphilic spin probes introduced into imbibed radicles of pea (Pisum sativum) and cucumber (Cucumis sativa) seeds. Survival following drying and a membrane integrity assay indicated that desiccation tolerance was present during early imbibition and lost in germinated radicles. In germinated cucumber radicles, desiccation tolerance could be re-induced by an incubation in polyethylene glycol (PEG) before drying. In desiccation-intolerant radicles, partitioning of spin probes into lipids during dehydration occurred at higher water contents compared with tolerant and PEG-induced tolerant radicles. The difference in partitioning behavior between desiccation-tolerant and -intolerant tissues could not be explained by the loss of water. Consequently, using a two-phase model system composed of sunflower or cucumber oil and water, physical properties of the aqueous solvent that may affect the partitioning of amphiphilic spin probes were investigated. A significant relationship was found between the partitioning of spin probes and the viscosity of the aqueous solvent. Moreover, in desiccation-sensitive radicles, the rise in cellular microviscosity during drying commenced at higher water contents compared with tolerant or PEG-induced tolerant radicles, suggesting that the microviscosity of the cytoplasm may control the partitioning behavior in dehydrating seeds.